TINJAUAN MENDALAM KURIKULUM PENDIDIKAN CINA: TREN, TANTANGAN, DAN HUKUM - Lestari, Fivi Setya; Hitta Alfi Muhimmah; Nurul Istiqfaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to take a deeper look at the education curriculum in China. This research discusses the curriculum, education system, trends, obstacles and educational laws in China. The method in this research uses literature study. Data collection in the form of educational documents was carried out using various existing website sources. The results of the discussion in this research are that China has a transcentralized education system, meaning starting from the central, provincial, municipal, district levels, and including autonomous regions at the municipal level. Then education in China consists of four sectors (1) basic education, (2) technical & vacational education, (3) higher education, and (4) adult education. Apart from these four sectors, there is also non-formal education, namely literacy education in order to eradicate illiteracy. The educational curriculum in China is more flexible to the needs of students and the welfare of teachers is given more attention